Concurrent Gliosarcoma and Choroid Plexus Carcinoma in a Cow. Issue 1 (January 2017) - Ortloff, A.; Neumann, J.; Illanes, O.
Summary: Brain tumours in cattle are uncommon and the spontaneous development of primary brain tumours of different histological types is rare in both man and animals. In man, multiple concurrent primary tumours of different types are occasionally described. We report the rare simultaneous occurrence of two different primary brain tumours, gliosarcoma and choroid plexus carcinoma, diagnosed by microscopical and immunofluorescence evaluation in an 8-year-old cow with a 2-month history of neurological disease. Gliosarcoma is a rare variant of glioblastoma multiforme, characterized by the presence of malignant glial cells and mesenchymal tissue. This tumour has not been reported previously in animals.